2017
DOI: 10.1001/jamaneurol.2017.1062
|View full text |Cite
|
Sign up to set email alerts
|

Brain Calcifications in Adult-Onset Genetic Leukoencephalopathies

Abstract: IMPORTANCE Adult-onset genetic leukoencephalopathies and leukodystrophies are increasingly recognized as a heterogeneous group of disorders with new diagnostic approaches and potential treatments. In the new era of genomics, the challenging interpretation of individual genetic variations requires an accurate phenotypic description and classification. Clinical and magnetic resonance imaging (MRI)-based approaches have been proposed to improve the diagnostic process of adult-onset leukoencephalopathies. Cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…7,17 Other series have suggested that small calcifications with a stepping stone distribution were characteristic of the disease, but their frequency has not been reported to date. 6,18 Here, we found calcifications in 4/6 patients who had undergone CT, stressing that they are likely frequent in ALSP. Of note, none of our patients with calcifications on CT had identifiable T2* hypointensities.…”
Section: Discussionmentioning
confidence: 53%
“…7,17 Other series have suggested that small calcifications with a stepping stone distribution were characteristic of the disease, but their frequency has not been reported to date. 6,18 Here, we found calcifications in 4/6 patients who had undergone CT, stressing that they are likely frequent in ALSP. Of note, none of our patients with calcifications on CT had identifiable T2* hypointensities.…”
Section: Discussionmentioning
confidence: 53%
“…The radiographic features of the 2 patients were also comparable with those of COL4A1/COL4A2 ‐related disease. Typical MRI features observed in COL4A1/COL4A2 ‐related disease include vascular leukoencephalopathy, porencephalic cavity, deep hemorrhages, microbleeds, lacunae, deep calcifications, dilated perivascular spaces, and intracranial aneurysms . In Patient 1, subependymal hemorrhage, porencephaly, microbleeds, and calcifications were observed.…”
Section: Discussionmentioning
confidence: 93%
“…Cysts.-Leukoencephalopathy with calcifications and cysts is a genetic disorder related to a mutation in the small nucleolar RNA, C/D box 118 (SNORD118) gene, which was identified recently. This disease is considered a microangiopathy, and as can be observed of other vasculopathies, asymmetric involvement of white matter may be a characteristic on MR images (Fig 17) (64)(65)(66).…”
Section: Leukoencephalopathy With Calcifications Andmentioning
confidence: 94%
“…The calcifications tend to be large and can be observed anywhere in the brain but mostly in the basal ganglia. Gadolinium contrast enhancement sometimes can be observed (64)(65)(66).…”
Section: Leukoencephalopathy With Calcifications Andmentioning
confidence: 99%